(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of social media marketing and service quality on the loyalty of visitors to Taman Pintar Yogyakarta which is mediated by word of mouth marketing. This research is a quantitative research, with a survey method. The sample in this study is the official Instagram audience of Taman Pintar Yogyakarta. The sampling technique used purposive sampling with a total of 145 people. The data collection technique uses a questionnaire distributed through Google forms which have been tested for validity and reliability. The data analysis technique used regression analysis. The results of the study show that: (1) Social Media Marketing has no positive effect on visitor loyalty at Taman Pintar Yogyakarta, this has been proven by the statistical results of the regression test obtained t count of 1.212 with a significance value of 0.227, therefore the significance value is greater than 0 0.05 (0.000 greather than 0.05), and the regression coefficient value is 0.106. (2) Service quality has a significant effect on visitor loyalty, this has been proven through the statistical results of the regression test obtained t count of 3,440 with a significance value of 0.001, because the significance value is less than 0.05 (0.001 less than 0.05), and the coefficient regression has a positive value of 0.259. (3) Word of Mouth has a significant effect on visitor loyalty, this is proven by the statistical results of the regression test obtained t count of 4.763 with a significance value of 0.000, because the significance value is less than 0.05 (0.000 less than 0.05), and the regression coefficient has a positive value of 0.418. (4) There is a significant influence of social media marketing on visitor loyalty through word of mouth at Taman Pintar Yogyakarta. This is proven from the calculation of the indirect effect of 0.228 which is greater than the direct effect of 0.120. (5) The influence of Service Quality on visitor loyalty through word of mouth is considered less significant, this is evidenced by the direct influence which is greater than 0.251 compared to the indirect effect which is only 0.091.